1994
DOI: 10.1089/aid.1994.10.701
|View full text |Cite
|
Sign up to set email alerts
|

Viral Leakage Risk Differences in Latex Condoms

Abstract: Through use of a new bacteriophage assay capable of detecting a single viral plaque-forming unit (PFU), viral leakage through multiple replicates of several types of latex condoms has been evaluated. Stocks were used that had been preserved from a previous large study in which viral leakage had been assessed preliminarily in several brands. In the present research, much larger numbers of replicates--on the order of magnitude of 100 condoms per brand--were used. Leakage was demonstrated in single production lot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Condom failure also appeared to account for a substantial proportion of seroconversions. The rate of condom failure in this study was within the range for breakage and/or slippage in men reported in the literature (2.7%-4.9% per person and 1.9%-8.0% per condom) [24][25][26][27][28][29][30] and is also supported by laboratory-based tests [31,32]. Condom failure rates may also be somewhat higher in anal sex than vaginal sex [24,26].…”
Section: Discussionsupporting
confidence: 85%
“…Condom failure also appeared to account for a substantial proportion of seroconversions. The rate of condom failure in this study was within the range for breakage and/or slippage in men reported in the literature (2.7%-4.9% per person and 1.9%-8.0% per condom) [24][25][26][27][28][29][30] and is also supported by laboratory-based tests [31,32]. Condom failure rates may also be somewhat higher in anal sex than vaginal sex [24,26].…”
Section: Discussionsupporting
confidence: 85%
“…No studies exist on their permeability to STI pathogens, although it is likely that they are at least as impermeable as condoms, which are also made of latex but thinner. Condoms have been tested in vitro for permeability to Chlamydia trachomatis, viruses and virus-sized particles [20][21][22][23][24] and except for one large study of aged condoms, 25 dams. If a piece tears during use it can easily be replaced.…”
Section: Evidence For the Effectiveness Of Dams In Preventing Hiv Tramentioning
confidence: 99%
“…Thus it happened that a fertility control prophylactic, the latex condom, was promoted as Thailand's national response towards the HIV epidemic, even though in vivo protective scientific evidence at the time was limited. [99][100][101][102][103][104] Observational data, [99][100][101][102][103][104] expert opinion and professional intuition, and the absence of alternatives convinced Dr Mechai the latex condom was the only available remedy. But for it to be effective, it needed to be used 100%.…”
Section: Preventionmentioning
confidence: 99%